Teaching Compassionate Mind Training to help midwives cope with traumatic clinical incidents. (2nd January 2021) - Martin, Caroline J Hollins; Beaumont, Elaine; Norris, Gail; Cullen, Gavin
Abstract : Compassionate Mind Training (CMT) is taught to cultivate compassion and teach midwives how to care for themselves. The need to build midwives' resilience is recognised by the Nursing and Midwifery Council (NMC), who advocate that mental health coping strategies be embedded into the midwifery curriculum. In this respect, CMT can be used as a resilience-building method to help midwives respond to self-criticism and threat-based emotions with compassion. The underpinnings of CMT involve understanding that people can develop cognitive biases or unhelpful thinking patterns, co-driven by an interplay between genetics and the environment. Within this paper, the underpinning theory of CMT and how it can be used to balance psychological threat, drive, and soothing systems are outlined. To contextualise the application to midwifery practice, a traumatic incident has been discussed. Teaching CMT has the potential to improve professional quality of life, and reduce midwife absence rates and potential attrition from the profession.